Strategi Pendidikan Agama Kristen Dalam Pembentukan Karakter Peserta Didik Konteks Moderasi Beragama - Anung, Soni I.; Belo, Yosia (IAKN Tarutung, 2025)
Religious moderation is very important in the world of education, with the existence of religious moderation can form an attitude of tolerance between students with each other. However, in the study there is data that confirms or provides an indication that there are still some people who do not have a high attitude of tolerance between religious communities. When it is known that the occurrence of an attitude of intolerance between one and another is also influenced by a lack of understanding of the concept of religious moderation correctly. Of course this attitude not only affects the school environment but also the wider community environment. Of course, the problems that occur are serious things that should be considered properly by teachers. Teachers have full responsibility in providing good education to their students and the environment in which they are located. Teachers not only provide general understanding or knowledge but also apply Christian values to the wider community so that they are able to live side by side accepting and respecting each other. The purpose of this study is to provide an understanding of how important the involvement of a teacher is in the world of education, because with the presence of a teacher can provide maximum understanding and education to everyone who experiences problems in themselves. The problem is not only faced or experienced by students but also experienced by the wider community. The writing method is to conduct library research through book sources, journals, websites as supporting references. The results of this study provide a good understanding of the importance of Christian values in religious moderation that contribute to the wider community to be able to live in tolerance. With the presence of a teacher can help various cases that often occur in the lives of every human being specifically regarding the issue of intolerance. Of course, with the presence of a teacher can provide Christian teachings and strengthen good faith to them so that every problem in life faced can be passed well without having to cause division between one another.